2017
DOI: 10.1111/jop.12666
|View full text |Cite
|
Sign up to set email alerts
|

Plasma IL‐8 signature correlates with pain and depressive symptomatology in patients with burning mouth syndrome: Results from a pilot study

Abstract: Overall, these findings indicate that plasma IL-8 profiles are dysregulated in BMS and that modulation of IL-8 production in the disorder may be a tool in the management of BMS symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 33 publications
4
67
0
Order By: Relevance
“…IL‐6 can exert both detrimental or beneficial effects on the nervous system; these effects may depend on the timing and level of IL‐6 expression (Biber et al, ; Wyss‐Coray & Mucke, ). Barry et al measured plasma levels of IL‐8 and showed that these levels were higher in BMS patients compared with controls; moreover, levels increased according to the intensity of pain and depression (Barry et al, ). However, this was only a pilot study involving a small number of individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐6 can exert both detrimental or beneficial effects on the nervous system; these effects may depend on the timing and level of IL‐6 expression (Biber et al, ; Wyss‐Coray & Mucke, ). Barry et al measured plasma levels of IL‐8 and showed that these levels were higher in BMS patients compared with controls; moreover, levels increased according to the intensity of pain and depression (Barry et al, ). However, this was only a pilot study involving a small number of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was only a pilot study involving a small number of individuals. As mentioned above, measurements of neuroinflammation‐associated molecules in saliva have yielded inconsistent results (Boras et al, ; Simcić et al, ; Suh et al, ), and studies using blood samples have sporadically suggested that some cytokines might exert some influence on BMS pathophysiology (Barry et al, ; Chen et al, ; Pekiner et al, ). Two genomic studies showed that IL‐1β polymorphisms are associated with the pathology of BMS (Guimarães et al, ; Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…James's Hospital Research Ethics committee (ref:2015‐09). Nine BMS patients and 8 healthy volunteers were recruited from Cork University Dental School and Hospital following informed written consent as described . As previously detailed, this BMS cohort demonstrated enhanced oral cavity pain as determined using a visual analogue scale (VAS), increased depressive symptomatology using the self‐rated 16‐item Quick Inventory of Depressive Symptomatology (QIDS‐SR 16 ) questionnaire and elevated plasma levels of the pro‐inflammatory chemokine, interleukin (IL)‐8 .…”
Section: Methodsmentioning
confidence: 99%
“…Nine BMS patients and 8 healthy volunteers were recruited from Cork University Dental School and Hospital following informed written consent as described . As previously detailed, this BMS cohort demonstrated enhanced oral cavity pain as determined using a visual analogue scale (VAS), increased depressive symptomatology using the self‐rated 16‐item Quick Inventory of Depressive Symptomatology (QIDS‐SR 16 ) questionnaire and elevated plasma levels of the pro‐inflammatory chemokine, interleukin (IL)‐8 . Following solid phase extraction on plasma, measurement of plasma PEA, OEA, AEA and 2‐AG was carried out using liquid chromatography–tandem mass spectrometry (LC‐MS/MS) as described previously, with minor modifications …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation